Pemberdayaan Guru dalam Implementasi Kurikulum 2013 di SD Negeri 4 Sragen - Wahyuni, Ninik, Dr. Tjipto Subadi, M.Si, Dr. Ahmad Muhibbin, M.Si (2017)
This study aims to: 1) Describe the empowerment of teachers in institutions in the implementation of Curriculum 2013 in SD Negeri 4 Sragen .; 2) Describe the personal empowerment of teachers in curriculum implementation in 2013 in primary school 4 Sragen. This study is a qualitative ethnographic research design. Informant in this research is the eadmaster and a teacher at the primary school 4 Sragen. Data was collected through interviews, observation and documentation. Data analysis techniques used in this study is an teractive model analysis, namely data collection, data reduction, data presentation and conclusion. Testing data using riangulation techniques. The results of this study: 1) Empowerment of teachers in institutions in the implementation of the curriculum in 2013 in primary school 4 Sragen has been good. This was indicated by 95% of teacher education meets the qualification standards, frequent activities in-house training to increase the competence of teachers, and routine supervision activities of the principal to monitor the activities of teacher performance. There was still some deficiencies in primary school 4 Sragen that has not had counseling teachers; 2) Empowerment of teachers in private in the implementation of the curriculum in 2013 in primary school 4 Sragen has been running well. At the beginning of the implementation of the curriculum still experiencing problems such as problems in the assessment, but because teachers continue to learn so that the obstacles that appear insurmountable. Evaluation of curriculum implementation in 2013 are being implemented by both the normative and internal summative schools and education authorities. Teacher empowerment activities to increase the competence of many carried out by teachers, including through continued studies to a higher level, active in KKG and IHT held the school and follow the assignment to training or a race. However, there are still shortcomings in the professional competence that teachers do not do research, as well as the teacher's ability to operate a computer is still lacking. Keywords: Empowerment, Teacher, Curriculum2013.